From Vision to Practice: Comparative Dynamics of Islamic Economics in Indonesia and Malaysia - sumarni sumarni; Ahmad rezy meidina; Andifa Dwi Fani; Nissa Ayu Marliana; Ikhdan Gimas Shufyansyah (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2025)
This paper aims to compare the development of Islamic economics in Indonesia and Malaysia, with emphasis on the banking sector as the core pillar. The study employs a descriptive-analytical method and a juridical-normative approach, analysing secondary data from official reports (OJK, Bank Negara Malaysia, IFSB), regulatory documents (Law No. 21/2008; Islamic Banking Act 1983; IFSA 2013), and peer-reviewed literature (2010–2023). Findings show that Indonesia’s Islamic banking assets grew by 13% in 2021, supported by digitalisation and market-driven strategies, though financial literacy remains low (below 40%). Malaysia, by contrast, records a 30% share of Islamic banking assets nationally and dominates the global sukuk market, strengthened by comprehensive regulation and the Shariah Advisory Council. The results imply that Indonesia must enhance literacy and financial inclusion, while Malaysia should innovate further to sustain its global leadership. This study contributes comparative insights for policymakers on aligning regulatory frameworks with maqāṣid al-sharīʿah and strengthening cross-border collaboration